Long-term ovarian neoplasm after liver transplantation: case report - Boin, Ilka de Fátima Santana Ferreira; Ataide, Elaine Cristina de; Sarian, Luiz Otavio Zanata; Costa, Larissa Bastos Eloy da; Andrade, Liliana Aparecida Lucci de Angelo; Munhoz, Derli Conceição (Brazilian Journal of Transplantation, 2021)
It is known that transplanted patients are at higher risk of developing malignant neoplasia. This fact is mainly due to the use of immunosuppressive drugs. We report the case of NAF, 38 years old, submitted to orthotopic liver transplantation in February, 1998, due to liver cirrhosis caused by hepatitis C virus. The investigation showed pelvic expansive lesion measuring 12.5x 9.0x 8.3 cm in contact with uterine wall. Ovary tumor whose freezing biopsy showed undifferentiated malignancy for an ovary laparotomy was chosen. Panhysterectomy and left oophorectomy were carried out, and histopathological specimen evidenced clear cell ovary adenocarcinoma, stage IA. Patient in follow-up for 3 and half years, with no evidence of recurrence and tumor markers within the normal range. The development of post-transplant neoplasms is a frequent complication and it is one of the main causes of late death in these patients. Avoiding excessive immunosuppression is the main recommendation although the prevalence was low the following laboratorial biomarker for tumor can be performed.